Brazil's new fish farming Decree threatens freshwater conservation in South America - Latini, A. O. (2021)
Aquaculture has tremendous importance in providing food for a growing world population. Nevertheless, unsustainable aquaculture causes nutrient buildup and favors biological invasions in natural habitats, demanding strategies to regulate such activity and therefore minimize environmental risks. Contrary to these concerns, the Brazilian Government has recently issued a new Federal Decree (10576/2020) encouraging the farming of invasive non-native species and excluding the Ministry of Environment from the legal process of issuing fish farming permits in reservoirs. The Decree increases the risk of non-native species establishment in inland waters at a national level and their propagation into neighboring countries, such as Argentina, Bolivia, Paraguay, and Uruguay. These consequences will endanger preserved freshwater ecosystems in the continent, including their native biodiversity, which represents both a problem of national sovereignty and a threat to the fundamental human right for a healthy environment. For this reason, the Decree contradicts the Brazilian Federal Constitution and conflicts with international treaties regulating invasive species and promoting sustainable development. It calls for immediate legal action and is yet another unfortunate sign of the increasing gap between science and decision making that has plagued the country in recent years.